Unveiling international new ventures' success: Employee's entrepreneurial behavior - Miguel A. Hernandez (Administrative Sciences, 2019)
New international ventures have become an important and growing role in the economics of a country. However, it seems that the literature on international entrepreneurship has paid little attention to their employees and their contribution to the success of these firms in international markets. The employee may be a key point in explaining their rapid and fruitful international development, i.e., increasing the international entrepreneurial orientation of the company. Using case study methodology, this investigation aims to unveil the human resource management in international new ventures, complete previous models explaining these organizations, and contribute to a better understanding of their international success. The findings show that the entrepreneurs aim to foster employee entrepreneurial behavior by implementing certain human resource practices.
Keywords: 350; international new venture; born global; employee entrepreneurial behavior; entrepreneurial orientation; intrapreneurship; human resource management; human resource practices